A multi-level network approach to spillovers analysis: An application to the Maltese domestic investment funds sector - Francesco Meglioli; Stephanie Gauci (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
In this paper we present a new approach to analyse the interconnectedness between a macro-level network and a local-level network. Our methodology is developed on the Diebold and Yilmaz connectedness measure and it considers the presence of entities within a global network which can influence other entities within their own local network but are not relevant enough to influence the entities which do not belong to the same local network. This methodology is then applied to the Maltese domestic investment funds sector and we find that a high-level correlation between the domestic funds can transmit higher spillovers to the local stock exchange index and to the government bond secondary market prices. Moreover, a high correlation among the Maltese domestic investment funds can increase their vulnerability to shocks stemming from financial indices, and therefore, investment funds may potentially become a shock transmission channel.
Keywords: C32; C58; G10; G23; 330; Network model; investment funds; interconnectedness; contagion; systemic risk; herding behaviour